MANAJEMEN TENAGA KEPENDIDIKAN/SDM DALAM PERSPEKTIF ILMU PENDIDIKAN - Sumual, Shelty D. M.; Rawis, Joulanda A. M.; Rompas, Elisa; Kambey, Allenita H. G.; Maukar, Abraham A. L. (Jurnal Manajemen Pendidikan, 2025)
Objective: This article aims to conceptually examine the management of educational support staff as a strategic component in educational governance, emphasizing the importance of competence, professionalism, and sustainable performance in ensuring the quality of academic and administrative services. Methods: This study employs a conceptual analysis approach supported by an extensive literature review of human resource management (HRM) theories, the Learning-Oriented Support System (LOSS) framework, as well as data-driven governance and service architecture models relevant to contemporary educational contexts. Results: The analysis reveals that educational support staff are no longer merely administrative implementers; rather, they have become an integral part of the learning system. Their roles contribute significantly to academic service effectiveness, strategic data management, and the strengthening of institutional learning capacity. Novelty: This article offers an integrated conceptual framework for managing educational support staff through a quality-oriented HRM approach, combining perspectives on competence, continuous learning support systems, and data-driven governance—an integration that has been largely overlooked in previous studies.